Matrix assisted laser desorption/ionization mass spectrometry of enzymatically synthesized RNA up to 150 kDa. - Kirpekar, F (1994)
Enzymatically synthesized RNA samples (in vitro transcripts) were analysed by matrix assisted laser desorption/ionization mass spectrometry (MALDI-MS). Spectra of RNA up to 150 kDA (461 nucleotides) are shown. Polymerase generated sample heterogeneity and its contribution to mass resolution are discussed. A time course exonuclease digest of a 55 nt in vitro transcript was analyzed to investigate the performance of MALDI-MS on complex mixtures. Based on these data, the analysis by MALDI-MS of DNA sequencing reactions, produced by the action of an RNA polymerase, is discussed.